PENERAPAN METODE DEMONSTRASI MELALUI KEGIATAN MERONCE UNTUK MENINGKATKAN PERKEMBANGAN MOTORIK HALUS - wulandari, ni made ari; Pudjawan, I Ketut (Universitas Pendidikan Ganesha, 2019)
This research purpose to find out the improvement of fine motor skill development through the applying demontration method by meronce activities to the children in group B1 at TK Kartika VII-3 Singaraja. Type of this research was classroom action research (CAR) which implemented two cycles. Subject of this research were 19 children of group B1 TK Kartika VII-3 Singaraja. Than the research data about fine motor skill development collected by using observation method. The data were analyzed by using descriptive statistics method, and descriptive quantitative analysis method. The result of analysis data shows there is an improvement of fine motor skill development when applying demontration method assisted by meronce activities raearches 22,43%. In the first cycle it’s reaches 59,58% which is low criteria increase in the second cycle to 82,01% which at high criteria. Thus it can be concluded that applying demontration method assisted by meronce activities can improve the fine motor skill development of the children in group B1 at TK Kartika VII-3 Singaraja.